2000
DOI: 10.1046/j.1523-536x.2000.00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcome After Previous Stillbirth Resulting from Causes Other Than Maternal Conditions and Fetal Abnormalities

Abstract: Pregnancy with a history of stillbirth as a result of causes other than maternal conditions and fetal abnormalities is a moderate risk state, with prematurity and low-birthweight rates somewhat higher than those in the general population. The overall probability of a favorable outcome is good. These findings may be useful in counseling pregnant women with a history of stillbirth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 20 publications
(19 reference statements)
5
51
1
2
Order By: Relevance
“…11 All studies of pregnancy outcome subsequent to unexplained stillbirth are reassuring in terms of perinatal mortality, but report increased rates of intervention and iatrogenic adverse outcomes such as prematurity, emergency cesarean section and post-partum hemorrhage. [7][8][9][10] There is likely to be a strong Hawthorne effect in such studies as the history of a previous stillbirth increases levels of surveillance in the next pregnancy and lowers the threshold to intervene. Optimizing fetal surveillance while minimizing the risk of false-positive results that might prompt unnecessary intervention presents the major challenge in this setting.…”
Section: Early Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…11 All studies of pregnancy outcome subsequent to unexplained stillbirth are reassuring in terms of perinatal mortality, but report increased rates of intervention and iatrogenic adverse outcomes such as prematurity, emergency cesarean section and post-partum hemorrhage. [7][8][9][10] There is likely to be a strong Hawthorne effect in such studies as the history of a previous stillbirth increases levels of surveillance in the next pregnancy and lowers the threshold to intervene. Optimizing fetal surveillance while minimizing the risk of false-positive results that might prompt unnecessary intervention presents the major challenge in this setting.…”
Section: Early Pregnancymentioning
confidence: 99%
“…Although the odds ratio for recurrence of stillbirths from all causes is almost five, 6 studies of pregnancy outcomes subsequent to unexplained stillbirth have not reported any increase in the risk of perinatal death. [7][8][9][10] However, those studies found that pregnancy after stillbirth is characterized by increased rates of induced labor, elective and emergency cesarean section, preterm birth and low birth weight. These adverse outcomes might be at least partly the result of obstetricians having a low threshold for intervention.…”
Section: Introductionmentioning
confidence: 99%
“…This relationship is true for stillbirths as well, although because of the relative rarity of recurrence, large populations are needed to demonstrate this relationship. A typical study showed that women with a stillbirth in the first pregnancy were more likely to have low-birth-weight (odds ratio (OR) 2.7) and preterm infants (OR 2.3) in the next pregnancy as well as an eight-fold increase in placental abruptions 18 . Freeman and associates found that women with a previous stillbirth, especially if Figure 1 Rate of stillbirth by gestational age, per 1000 live fetuses at that gestational age.…”
Section: Risk Factors For Stillbirthmentioning
confidence: 99%
“…5 To our knowledge, this is the first study that has exlusively assessed healthcare utilisation in the pregnancy following stillbirth compared with other pregnant women. So far, there have been few large-scale studies on mode of delivery in pregnancies following stillbirth, 17,18 particularly stillbirths of all causes. 19 Hence, this study adds to a limited body of evidence.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…17 Studies from Finland and Scotland reported similar findings. 18,19 Whether anxiety, fear or dread of childbirth partially accounts for more frequent use of interventions in pregnancies subsequent to stillbirth, however, remains unknown.…”
Section: Introductionmentioning
confidence: 99%